The diphenylpyrazole compound anle138b blocks Aβ channels and rescues disease phenotypes in a mouse model for amyloid pathology. Issue 1 (5th December 2017) - Martinez Hernandez, Ana; Urbanke, Hendrik; Gillman, Alan L; Lee, Joon; Ryazanov, Sergey; Agbemenyah, Hope Y; Benito, Eva; Jain, Gaurav; Kaurani, Lalit; Grigorian, Gayane; Leonov, Andrei; Rezaei‐Ghaleh, Nasrollah; et al.
Abstract: Alzheimer's disease is a devastating neurodegenerative disease eventually leading to dementia. An effective treatment does not yet exist. Here we show that oral application of the compound anle138b restores hippocampal synaptic and transcriptional plasticity as well as spatial memory in a mouse model for Alzheimer's disease, when given orally before or after the onset of pathology. At the mechanistic level, we provide evidence that anle138b blocks the activity of conducting Aβ pores without changing the membrane embedded Aβ‐oligomer structure. In conclusion, our data suggest that anle138b is a novel and promising compound to treat AD‐related pathology that should be investigated further. Synopsis: Although a substantial amount of data point to a causative role of amyloid beta and Tau pathology in Alzheimer's disease (AD) pathogenesis, no effective therapy has been developed. This study reports that anle138b blocks amyloid beta channels formation and ameliorates disease pathology. Amyloid beta peptides form conducting channels in neuronal membranes. Amyloid beta channels lead to a loss of cellular homeostasis and memory impairment. The small molecule compound anle138b blocks amyloid beta channels and ameliorates disease phenotypes in animal models. The small molecule compound anle138b also reinstates homeostasis in model of Tau‐pathology. Abstract : Although a substantial amount of data point to a causative role of amyloid beta and Tau pathology in Alzheimer's disease (AD) pathogenesis, no effective therapy has been developed. This study reports that anle138b blocks amyloid beta channels formation and ameliorates disease pathology.